Efektivitas Pemakain Jamur MG3T untuk pertumbuhan Alpukat Mentega (Persea americana), Durian (Durio zibethinus) dan Jambu Air Kancing (Syzygium aqueum): Effectiveness of using MG3T fungi for the growth of Butter Avocado (Persea americana), Durian (Durio zibethinus) and Button Water Apple (Syzygium aqueum) - Sufindra, Annas Aji; Turmuji, Turmuji; Priyanto, Teguh; Gumari, Febram; Hambali, Muhamad David; Bima, Farizalman Aria; Ahmad, Riza Zainuddin (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
Post-mining land reclamation must be carried out by planting vegetation, including fruits as inserts between fast and slow-growing plants. This study aims to evaluate three treatments on the growth of butter avocado trees, durian trees, and button water apple trees at the PT Suprabari Mapanindo Mineral Nursery for six months in 2025. The treatments tested included: (1) MG3T of fungi (Gliocladium sp., Mycorrhiza sp., Trichoderma spp.); (2) PT SMM standard; and (3) control. Leaf, stem, and root parameters were observed for 12 weeks. Generally, the combination of fungi treatment increased most of the growth. However, the PT SMM standard treatment was superior in durian stem diameter and the number of butter avocado leaves. Statistical significance (p<0.05) was found in the number of leaves of button water apple trees (fungus combination), durian tree stem diameter (PT SMM standard), durian tree stem height (fungus combination), and the number of root branches of button water apple trees (fungus combination).